Do Intangibles Influence the Market Rate of Return? Panel Data Analysis of the Newconnect Market in Warsaw - Bolek, Monika; Lyroudi, Katerina (European Scientific Journal, ESJ, 2017)
Financial markets in most countries are changing by opening new sections of exchange for companies in early stage of development. Nowadays young companies are looking for capital from investors who are interested in financing innovative and risky projects, expecting higher rate of return. Alternative systems of trading are becoming more and more popular. This sector is growing rapidly, mostly supporting the commercialization of innovations by small and medium companies. Based on the above, we can state that innovativeness influences the rate of return of young and fast growing companies. The innovativeness is associated with the intellectual capital of a company which can be proxied and measured by its intangible assets listed on the balance sheet. Hence, we form our research question and main testable hypothesis that the level of a firm’s intangible assets affects positively the rate of return on the market. We applied panel data regression analysis in various forms and we found that the cash flow is correlated positively and significantly with the rate of return while other variables like intangibles could affect the rate of return negatively and the size variable positively in a sample of small and medium sized companies. However, the model parameters are questionable since it is well known that the behavior of young companies is unpredictable.